Qualification of IjtihÉd in Present Era - SAJILA KAUSAR, (Hamdard Islamicus, 2018)
Allah al-Mighty sent the human beings in this universe with a complete code of guidance in the form of the Qur’Én and Sunnah of the Prophet (œ). Both these sources guide different fields of life principally. The commandments of the Qur’Én and Sunnah are unchangeable. No one can ignore them, but the problems of life are endless. And solution of all these problems cannot be presented in a single book. So, the Shar‘Êah has introduced the principle of ijtihÉd to resolve all these issues. IjtihÉd is not to create something new in religion rather it is to tell the point of view of religion about the newly born problems. But it should also be kept in mind that to perform ijtihÉd there are certain terms and conditions, which if not fulfilled will spoil the concept of ijtihÉd. These terms and conditions have been discussed and modified time to time. The former scholars of Islam have a detailed discussion on this topic. The scholars of present era also have focused on this topic and have presented its requirements in the current era which are going to be discussed in the coming lines.